2020
DOI: 10.1016/j.jtauto.2020.100035
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-xL overexpression decreases GILZ levels and inhibits glucocorticoid-induced activation of caspase-8 and caspase-3 in mouse thymocytes

Abstract: Glucocorticoids promote thymocyte apoptosis and modulate transcription of numerous regulators of thymic apoptosis. Among these, glucocorticoid-induced leucine zipper (GILZ) is strongly upregulated in the thymus. We have previously demonstrated that GILZ decreases Bcl-xL expression, activates caspase-8 and caspase-3, and augments apoptosis in mice thymocytes. To better understand the causal links between glucocorticoids, GILZ, Bcl-xL, caspase-8, and caspase-3, we analyzed the thymocytes of Bcl-xL-overexpressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
2
3
0
1
Order By: Relevance
“…On the other hand, death receptors activate the caspase 8, which later is activates caspase 3 [24]. Henceforth, caspase 3 activates the intrinsic pathway [24]. In our study, the fold increase in caspase 9, 8 and 3 mRNA expression were very minute in CRL-4010 normal cells, whereas that in SKBR3 cells became upregulated by more than 4 folds, emphasizing the more selective action of AuNPs on cancer cells (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…On the other hand, death receptors activate the caspase 8, which later is activates caspase 3 [24]. Henceforth, caspase 3 activates the intrinsic pathway [24]. In our study, the fold increase in caspase 9, 8 and 3 mRNA expression were very minute in CRL-4010 normal cells, whereas that in SKBR3 cells became upregulated by more than 4 folds, emphasizing the more selective action of AuNPs on cancer cells (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Apaf1 stimulates caspase 9 which causes activation of caspase 3 that plays a crucial role in cell death [23]. On the other hand, death receptors activate the caspase 8, which later is activates caspase 3 [24]. Henceforth, caspase 3 activates the intrinsic pathway [24].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of caspase 3 is a sign that apoptosis has entered an irreversible stage (30). Ligustrazine promotes the activation of caspase 3, which can inhibit tumor cell propagation and metastatic ability (31,32). In our study, Fas activated caspase 8 and promoted the initiation of apoptosis, which in turn triggered caspase 3 expression and regulated the caspase pathway to promote apoptosis in A549 cells.…”
Section: Discussionsupporting
confidence: 48%
“…Several studies have demonstrated that GILZ exerts anti-inflammatory activity, often acting as a mediator of glucocorticoid actions but without the glucocorticoid-derived side effects [ 6 , 7 , 8 , 9 , 10 ]. While almost ubiquitously expressed, GILZ is rapidly induced by glucocorticoids primarily in immune cells of the adaptive and innate system and regulates their cellular functions (e.g., activation, differentiation, and apoptosis) [ 3 , 11 , 12 , 13 , 14 , 15 , 16 ]. Within the cells of the innate immune system, few studies have investigated the function of GILZ in neutrophils.…”
Section: Introductionmentioning
confidence: 99%